2021
DOI: 10.1111/evo.14360
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant RNA splicing due to genetic incompatibilities in sunflower hybrids

Abstract: Genome-scale studies have revealed divergent mRNA splicing patterns between closely related species or populations. However, it is unclear whether splicing differentiation is a simple byproduct of population divergence, or whether it also acts as a mechanism for reproductive isolation. We examined mRNA splicing in wild × domesticated sunflower hybrids and observed 45 novel splice forms that were not found in the wild or domesticated parents, in addition to 16 high-expression parental splice forms that were abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Previous studies showed how isoforms with species‐specific expression resulted in functional divergence between proteins of the same family and hence drove divergence of phenotypic traits between species (Huang et al., 2021; Smith et al., 2018; Smith et al., 2021; Thatcher et al., 2014; Zhang, Wang, et al., 2017). Also, when comparing isoforms between the two Nelumbo species, we identified 4854 N. nucifera genes and 4424 N. lutea genes that gave rise to lineage‐specific isoforms in each of their respective lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed how isoforms with species‐specific expression resulted in functional divergence between proteins of the same family and hence drove divergence of phenotypic traits between species (Huang et al., 2021; Smith et al., 2018; Smith et al., 2021; Thatcher et al., 2014; Zhang, Wang, et al., 2017). Also, when comparing isoforms between the two Nelumbo species, we identified 4854 N. nucifera genes and 4424 N. lutea genes that gave rise to lineage‐specific isoforms in each of their respective lineages.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, the domestication process has generated multiple examples of rapid adaptation via AS [19][20][21][22]. One example of this is the EARLY MATURITY 8 (EAM8) gene in barley [19], which is an orthologue of the circadian core component EARLY FLOWERING 3 (ELF3) in Arabidopsis thaliana.…”
Section: Alternative Splicing Isoforms As Source Of Transcriptome And...mentioning
confidence: 99%
“…Subsequent steps to filter the transcriptome, retain high confidence alternative isoforms, and test for differential splicing were the same as described previously (Smith et al, 2021). Briefly, we required alternative isoforms to align to the same genomic region, otherwise we labeled the isoforms as separate genes.…”
Section: Differential Splicingmentioning
confidence: 99%